2021
DOI: 10.2147/rmhp.s339274
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Knowledge, Attitudes, and Self-Reported Practices Among Medical Staff in China Before, During and After the COVID-19 Pandemic

Abstract: Purpose To compare food safety knowledge, attitudes, and self-reported practices among medical staff in China before, during, and after the COVID-19 pandemic. Patients and Methods The questionnaire was anonymous. All respondents were Chinese medical personnel. A Chi-square contingency table was used to compare the knowledge and attitudes of Chinese medical staff before, during and after COVID-19. R statistical software (v4.0.0) was used for analysis. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous studies have also confirmed this view. A study by Liu et al (36) revealed that healthcare workers are more concerned about food safety following a pandemic outbreak. A meta-analysis also suggested that interventions aimed at lifestyle change are more likely to improve nurses' HRQoL (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also confirmed this view. A study by Liu et al (36) revealed that healthcare workers are more concerned about food safety following a pandemic outbreak. A meta-analysis also suggested that interventions aimed at lifestyle change are more likely to improve nurses' HRQoL (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although the real cause of Covid 19 remains debatable, many people believe Covid-19 has close associations with what people choose to eat, such as wild animals like bats [16]. Hence, consumers today are more concerned with food safety than ever, which makes establishing a supply chain that offers safe food to customers essential.…”
Section: The Application Of Iot In the Food Grocery Supply Chainmentioning
confidence: 99%
“…It is imperative to assess nursing and medical students' knowledge, attitudes, and practices regarding food safety, given their apparent duties to contribute to a healthier generation by minimizing the risk of foodborne diseases (Luo et al, 2019). Nursing and medical students who are future medical professionals; patients often acquire knowledge regarding food safety from medical professionals and they can contribute to prevention and health promotion by improving patients' awareness of food safety (Luo et al, 2021). Nursing and medical students are involved in food preparation in the household, and nurses are considered caregivers and have direct contact with patients at each mealtimes.…”
Section: Introductionmentioning
confidence: 99%